Large Angular-scale Multipoles at Redshift ∼ 0.8 - Tiwari, P.; Aluri, P.K. (Institute of Physics Publishing, 2019)
We prepare the full sky radio galaxy map (|b| > 10°), using the north NRAO VLA Sky Survey and south Sydney University Molonglo Sky Survey galaxy catalogs, and study the large-scale multipole anomalies. These galaxies are roughly at redshift z ∼ 0.8 and are therefore tracing the matter distribution at very large scales. The quadruple and octopole from the radio galaxy catalog are consistent with λCDM for a reasonable value of galaxy bias and we do not find dipole-quadruple-octopole alignment as seen in cosmic microwave background (CMB) emperature maps. The quadrupole direction is roughly 46° away from dipole, and the octopole direction is approximately 33° from dipole. The angle between quadrupole and octopole is around 70°. We have large errors in multipole directions due to shot noise. However, with the data that is currently available we do not find any significant alignment between the l = 1, 2, 3 modes. The magnitude of all multipoles, except dipole, are roughly consistent with λ CDM for reasonable galaxy bias. The dipole magnitude remains inconsistent with CMB as reported in previous studies. Our findings may impose stringent constraints on cosmological models with large-scale anisotropy features. © 2019. The American Astronomical Society. All rights reserved.
Keywords: dark matter – galaxies; active – galaxies; high-redshift – large-scale structure of universe